Crystallization Study of Pb Additive Se-Te-Ge Nanostructured Alloys using Non-isothermal Differential Scanning Calorimetry - Patial, Balbir Singh; Sharma, Neha; Bhardwaj, Suresh; Thakur, Nagesh (Nanofabrication, 2022)
Nanotechnology started a new era in research and continuous escalations due to its potential applications. In modern optoelectronics, Pb additive nano-chalcogenides are becoming promising materials. For a memory and switching material, the thermal stability and glass-forming ability are vital, and the glass should be thermally stable from a technological point of view. This research article investigates the thermal behaviour of bulk (Se80Te20)94-xGe6Pbx (x = 0, 2, 4 and 6) samples synthesized using the melt quench procedure non-isothermal differential scanning calorimetry at four heating rates from 5 to 20°Cmin-1. Further, the overall crystallization study, which includes thermal stability, ease of glass formation, fragility, glass relaxation and glass-crystallization transformation kinetics of investigated alloys using different empirical formalisms, is reported and discussed. Compositional and heating rate dependence of recorded characteristic temperatures and other deduced parameters of reheated alloys are also discussed. The correlation between deduced parameters is also established to define the utility of these materials in practical applications.